The incidence of drug-induced interstitial lung disease caused by epidermal growth factor receptor tyrosine kinase inhibitors or immune checkpoint inhibitors in patients with non-small cell lung cancer in presence and absence of vascular endothelial growth factor inhibitors: a systematic review - Fujiwara, Yutaka; Shimomura, Kazuhiro; Yamaguchi, Teppei; Shimizu, Junichi; Watanabe, Naohiro; Matsuzawa, Reiko; Murotani, Kenta; Horio, Yoshitsugu (Frontiers in Oncology, 2024)
Interstitial lung disease (ILD) or pneumonitis caused by epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKI) or immune checkpoint inhibitors (ICI) is a major concern in the treatment of non-small cell lung cancer (NSCLC). Whether the addition of vascular endothelial growth factor (VEGF) and VEGF receptor (VEGFR) inhibitors can reduce the incidence of drug-induced ILD remains unclear. We conducted a systematic review to assess the incidence of ILD induced by EGFR-TKIs or ICIs in the presence or absence of VEGF/VEGFR inhibitors in relevant randomized trials between January 2009 and October 2023. The primary outcome was the odds ratio for the incidence of ILD in all patients worldwide and Asians. Secondary outcomes were the odds ratios (ORs) of the incidence at grade-3 or higher ILD in all patients worldwide and Asians. We identified 13 randomized studies, one sub-analysis in the EGFR-TKI group, and three randomized studies in the ICI group. In the EGFR-TKI group, the OR of ILD incidence at any grade with VEGF/VEGFR inhibitors was 0.54 (95% CI, 0.32-0.90; p = 0.02), which represented a significantly lower incidence than that without VEGF/VEGFR inhibitors. Contrarily, the OR of ILD incidence at grade ≥ 3 with VEGF/VEGFR inhibitors was 1.00 (95% CI, 0.43-2.36; p = 0.99). In all subjects in the ICI group, the OR of ILD incidence at any grade with VEGF/VEGFR inhibitors was 0.78 (95% CI, 0.51-1.21; p = 0.27). The systematic review demonstrated that the addition of VEGF/VEGFR inhibitors could reduce the incidence of drug-induced ILD at any grade caused by EGFR-TKI in patients with NSCLC but could not reduce that at grade ≥ 3. The ILD induced by ICIs remains undetermined owing to the limited number of randomized trials for which ILD data are available.